Everyday enlightenment the twelve gateways to human potential - Millman, Dan (Hodder & Stoughton, 1998)
This text is the culmination of Dan Millman's insights and explorations of human potential. The process, he believes, is a journey of awakening, comprising of 12 gateways which must be passed to fulfill potential in relationships, work, finance and health.